Safety Assessment of Arctium lappa L. Fruit Extract in Female Wistar Rats: Acute and Repeated Oral Toxicity Studies - Maedeh Yaghoubi; Zahra Mousavi*; Tayebeh Rastegar; Gholamreza Amin (Iranian Society of Pharmacognosy, 2019)
Background and objectives: Arctium lappa belonging to the Compositae (Asteraceae) family has been used as a medicinal and nutritional supplement in the world. The fruits, leaves and roots of the plant are well-known for their pharmaceutical effects. Toxicity of the fruit's extract in female rats was investigated in the present study. Methods: To assess the toxicity profile of Arctium lappa fruit extract (ALFE), it was administered to rats by gavage in acute and repeated models. The animals were divided into two groups: control and test groups. In the acute toxicity model, 1000 and 5000 mg/kg ALFE were administered to the animals. Toxic symptoms, body weight, death and abnormal behaviors were observed for 14 days. In the repeated toxicity model, ALFE (300 mg/kg) was daily administered for 4 weeks. Biochemical and histopathological changes were assessed and compared with the control group. Statistical significance was determined by one-way analyses of variance, followed by the Tukey test using GraphPad Prism 6. Results: No mortality was noticed in the acute test; therefore, the oral LD50 value determined in the female rats was greater than 5000 mg/kg. In the repeated test, the animals received ALFE (300 mg/kg) and no mortality was observed. The hematology and serum chemistry parameters showed no statistically significant changes.  The histopathological studies revealed evidences of microscopic lesions in two main organs lungs and small intestine. Conclusion: The results indicated that the oral acute toxicity of ALFE in the rats was of a low order with LD50 being more than 5000 mg/kg. Moreover, they revealed slight tissue damage to several organs when sub-chronically administered at a dose of 300 mg/kg.